Spore co-editor receives Boerma award - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Michael Pickstock, Director of Media Projects, the company responsible for the English edition of Spore, is joint recipient of this year's Boerma Award. Given annually by FAO, the Boerma Award is presented 'For journalistic work which has helped to...